2018
DOI: 10.1097/prs.0000000000004827
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Mastectomy Improves Satisfaction with Body and Psychosocial Function in Trans Men: Findings of a Cross-Sectional Study Using the BODY-Q Chest Module

Abstract: Evidence-Based Outcomes Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 16 publications
0
32
1
Order By: Relevance
“…Clinically significant reductions in psychopathology and substance abuse following GAS have been documented in the literature, 28,29 including studies specific to masculinizing mastectomy. 6,8 As such, continued investigation into the safety, efficacy, and epidemiology of this procedure is essential to facilitate the development of optimal and ethical management strategies. However, there are numerous challenges associated with research into this population and procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically significant reductions in psychopathology and substance abuse following GAS have been documented in the literature, 28,29 including studies specific to masculinizing mastectomy. 6,8 As such, continued investigation into the safety, efficacy, and epidemiology of this procedure is essential to facilitate the development of optimal and ethical management strategies. However, there are numerous challenges associated with research into this population and procedure.…”
Section: Discussionmentioning
confidence: 99%
“…5 Importantly, masculinizing chest reconstruction has been shown to significantly improve psychosocial functioning and quality of life. 68 Expanded access to care and improvements in social stigma have led to a substantial rise in the number of gender-affirming surgeries (GAS) performed in the United States over the past 5 years, opening up new avenues for quality improvement. 9 Ongoing evaluation and review of epidemiologic and postoperative complications data are imperative to maintaining high standards of care and identifying demographic disparities.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to previous PRO−based cross−sectional studies [10,11,53], the relationships identified using correlation coefficients should be interpreted as associations and not causal relations [33]. The present study may act as a data reference to generate hypotheses that justify further investigations.…”
Section: Discussionmentioning
confidence: 84%
“…Since no prior investigation employed the FACE-Q questionnaire and 3D morphometry for analysis of a cohort of patients, we could not perform a direct comparative appraisal of the current versus former findings. The generalizability of our findings cannot be assumed, as all included patients were treated by particular procedural strategies, including the digital occlusion set up, virtual surgery, surgeryfirst model, and two-jaw orthognathic surgery with single-splint technique 3,[45][46][47][48][49] . We enrolled a restricted final sample as only matched patients and controls were included for analysis.…”
Section: Discussionmentioning
confidence: 99%